An Inclusive Early Warning System and Community Preparedness in the Mount Merapi Eruption-Prone Area - Nugroho, Ariyanto; Rahmuniyati, Merita Eka; Sahayati, Sri; Rusyani, Yelli Yani; Farida, Ani; Sari, Ara’ Afliyatun Nur (Program Studi Ilmu Kesehatan Masyarakat, Universitas Jambi, 2026)
One of Indonesia's most active volcanoes, Mount Merapi, puts nearby residents at risk. Risk reduction strategies require understanding readiness factors. This study aims to identify the determinants of disaster preparedness among communities living in the Mount Merapi hazard area, with a particular focus on examining the influence of socio-demographic factors and geographical proximity through a mixed-method approach. This research was conducted among 122 residents living in the Mount Merapi area and indepth interview with informants. Preparedness level (low, moderate, high) was assessed using a structured index, measured by knowledge and attitude (KA); emergency planning (EP), Warning System (WS), dan Resource Mobilization Capacity (RMC). To find independent predictors of high preparation, the Chi-square test and multivariable logistic regression were used. Variables included age, gender, occupation, length of residence, and distance from Mount Merapi. Chi-square test showed significant associations between preparedness and gender (χ² = 6.51, p = 0.039), occupation (χ² = 18.345, p = 0.049), distance to Mount Merapi (χ² = 14.768, p = 0.005), and length of residence (χ² = 19.655, p = 0.003). Multivariable analysis revealed that gender (B = 1.550, p = 0.009, OR = 4.713) and distance to Mount Merapi (B = –1.416, p = 0.023, OR = 0.243) were independent predictors of preparedness. Based on in-depth interviews with informants, residents who received disaster preparedness bag training exhibited effective emergency planning. Gender and proximity to the hazard drive disaster preparedness. Training, simulation exercises, and community education programs should actively incorporate men and women to improve preparedness knowledge and reaction skills and build preparedness strategies for areas near Mount Merapi.